Engineering geological behaviour of volcanic formations. References to instability phenomena and town planning in Lesvos Island, Greece - Saroglou, H. (Bulletin of the Geological Society of Greece, 2012)
The volcanic formations have varying behaviour between rock and soil depending on their geological origin, weathering degree and fracturing degree. The engineering behaviour and weathering classification of these formations is briefly reviewed. Slope stability problems in these rocks have either the form of soil type instabilities (mainly circular failures and creep phenomena) or rock instabilities such as rock sliding on discontinuities and rockfalls. These slope instabilities pose significant problems to human activities. A case study referring to slope stability problems in different volcanic formations is given from the area of Petra municipality in Lesvos Island, Greece. The main volcanic formations in the study area are rhyodacitic and latiandesitic lavas, having rock behaviour and perlites, silicated lavas and pyroclastics, which have a soil like behaviour. Additionally, profiles of totally weathered andesites resulting to clay rich soils are frequently encountered. The mechanism of the anticipated instability phenomena are presented and analyzed. Finally, a simple vulnerability map for instabilities was prepared, which can assist in town planning. Based on the field observations, the potential for occurrence of instability phenomena is related to the following factors: a) Slope aspect and b) geological nature of volcanic rocks (weathering degree and permeability).